Halving of Swiss glacier volume since 1931 observed from terrestrial image photogrammetry - Mannerfelt, Erik Schytt; Dehecq, Amaury; id_orcid:0 000-0002-5157-1183; Hugonnet, Romain; id_orcid:0 000-0002-0955-1306; Hodel, Elias; id_orcid:0 000-0003-0988-0545; Huss, Matthias; id_orcid:0 000-0002-2377-6923; Bauder, Andreas; id_orcid:0 000-0001-7197-7706; Farinotti, Daniel; et al. (Copernicus, 2022)
The monitoring of glaciers in Switzerland has a long tradition, yet glacier changes during the 20th century are only known through sparse observations. Here, we estimate a halving of Swiss glacier volumes between 1931 and 2016 by mapping historical glacier elevation changes at high resolution. Our analysis relies on a terrestrial image archive known as TerrA, which covers about 86 % of the Swiss glacierised area with 21 703 images acquired during the period 1916–1947 (with a median date of 1931). We developed a semi-automated workflow to generate digital elevation models (DEMs) from these images, resulting in a 45 % total glacier coverage. Using the geodetic method, we estimate a Swiss-wide glacier mass balance of −0.52 ± 0.09 m w.e. a−1 between 1931 and 2016. This equates to a 51.5 ± 8.0 % loss in glacier volume. We find that low-elevation, high-debris-cover, and gently sloping glacier termini are conducive to particularly high mass losses. In addition to these glacier-specific, quasi-centennial elevation changes, we present a new inventory of glacier outlines with known timestamps and complete attributes from around 1931. The fragmented spatial coverage and temporal heterogeneity of the TerrA archive are the largest sources of uncertainty in our glacier-specific estimates, reaching up to 0.50 m w.e. a−1. We suggest that the high-resolution mapping of historical surface elevations could also unlock great potential for research fields other than glaciology. ISSN:1994-0416 ISSN:1994-0424